Performance assessment and indicators for agricultural water management - a review - Ahmad, Muhammad Tajuri (2024)
The complexity of irrigation systems and the need to adapt them to uncertainties requires developing approaches to synthesize their performances. This paper reviews performance assessment and indicators for agricultural water systems. It is aimed at finding various methods and indices used for irrigation performance assessment and standard classes for their characterization. The global application of the metrics was also documented. Adopting a systematic review approach, peer-reviewed journal articles published in the English language in the last two decades (1 March 2001 to 31 December 2020) were surveyed. Case studies were presented demonstrating the application of the indicators. The study revealed a lack of standardization and the use of a wide range of indicators among others, and recommended representing certain indicators as single. However, this review considered one indicator as the best. Suggestions for further studies were made.